0007 Transfer Of Skills Of Managing Sepsis From A Simulated Lab To The Clinical Environment: A Work In Progress. (1st November 2014) - Kasfiki, Eirini Vasileiou; Aslam, Imran; Thakur, Mukesh; Weerasakera, Chaminda; Purva, Makani
Abstract : In simulation based research in medicine, there is relative paucity of proof that simulation improves patients' care. That stems from the difficulty of designing and executing a transitional research type 2/3 within the medical field. 1 In our study we aim to demonstrate the transfer of skills acquired in simulation to the clinical setting in the management of sepsis. Sepsis was chosen as a condition for its high mortality and poor treatment rates. 2 Methodology: Ethics approval was obtained. Fourteen junior doctors in our hospital were given an initial lecture on sepsis management, and were all individually videorecorded treating a patient with sepsis. Consent was obtained from doctors, nurses and patients. Trainees were then randomly allocated into two groups. One group received simulation training on sepsis management and the control group attended a lecture, based on the Sepsis 6 (2). All fourteen participants were again videorecorded treating patients with sepsis. Currently all the videos are being watched by two independent and blinded assessors (consultant physicians) and participants' technical and non-technical performance is scored against two validated tools (sepsis 6, and miniCex) Results: Statistical analysis (ANOVA) will be used to look for correlations between difference in performance in the three groups (pre intervention, post simulation, and post lecture-control group). We will be able to present our initial results in the conference. Impact: Our study is one of the first to capture real time transfer of skills from a simulation to a real environment in medicine. We hope that our results will pave the way for further research in this area. The study is uni-centred and the subject number is small, but we tried to limit this problem by designing a sound research protocol and double blind the process, as the assessors of the videos don't know which group the candidates belong to. References: McGaghie WC, Draycott TJ, Dunn WF, Lopez CM, Stefanidis D, ''Evaluating the Impact of Simulation on Translational Patient Outcomes'', Simulation Healthcare Journal 2011;6:42–47 Eichacker PQ, Natanson C, Danner RL, "Surviving sepsis-practice guidelines", New England Journal of Medicine 2006;355:1640–1642